1992
DOI: 10.1136/bmj.304.6821.227
|View full text |Cite
|
Sign up to set email alerts
|

Health promotion in the general practice consultation: a minute makes a difference.

Abstract: Objective-To see whether extending appointment length from seven and a half minutes or less to 10 minutes per patient would increase health promotion in general practice consultations.Design-Controlled trial of 10 minute appointments. Consultations were compared with control surgeries in which the same doctors booked patients at their normal rate (median six minutes per patient).Setting-10 general practices in Nottinghamshire. Subjects-16 general practitioners were recruited. Entry criteria were a booking rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 11 publications
1
32
1
3
Order By: Relevance
“…1 Prior studies have found that more time spent with patients may improve patient satisfaction, patient education, and clinical outcomes, and reduce inappropriate prescribing. [19][20][21][22] In the wake of the 2003 and 2011 work hours limitations, the proportion and absolute amount of time spent in direct patient care has dropped in both Fletcher's study 14 and this study. As a result, the total time residents can expect to spend learning from patients appears to have decreased, which may affect the quality of the patient-physician relationship and the quality of care delivered.…”
Section: Discussionmentioning
confidence: 72%
“…1 Prior studies have found that more time spent with patients may improve patient satisfaction, patient education, and clinical outcomes, and reduce inappropriate prescribing. [19][20][21][22] In the wake of the 2003 and 2011 work hours limitations, the proportion and absolute amount of time spent in direct patient care has dropped in both Fletcher's study 14 and this study. As a result, the total time residents can expect to spend learning from patients appears to have decreased, which may affect the quality of the patient-physician relationship and the quality of care delivered.…”
Section: Discussionmentioning
confidence: 72%
“…for GPs in this location in the Islamic Republic of Iran. Although consultation time in our study was shorter than in several other developed and developing countries [5,15,16,23,25], knowledge about the use and precautions of prescribed drugs and satisfaction of patients was comparable with some other countries [1][2][3]26]. Others have suggested that while consultation time is an important indicator of quality of care the impact of cultural and sociopsychological factors should not be underestimated in determining patient satisfaction and quality of health care services [13,27,28].…”
Section: Consultation Lengthmentioning
confidence: 63%
“…Doctors with longer consultation times tend to diagnose illnesses more precisely, prescribe fewer drugs and present better health advice to their patients [14][15][16]. Other studies have looked at correlations between aspects of the consultation process and the quantity and quality of prescribed drugs in each prescription [17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…One study suggests that physicians in high-volume practices sacrifice the delivery of preventive services and have less positive relationships with their patients (42). Though interventions to increase appointment duration did not change prescribing rates or patient satisfaction (43), they can increase physician health education (44) and prevention activities (45), and promote psychosocial discussions (45). Results from this study suggest that office visits may need to be restructured in order to promote improved communication about new prescriptions.…”
Section: Practice Implicationsmentioning
confidence: 94%